Estimation and analysis of business process models similarity in enterprise continuum repository - Kopp, A. M.; Orlovskyi, D. L. (Національний технічний університет України "Київський політехнічний інститут ім. Ігоря Сікорського", 2018)
This paper considers the problem of the store, share, and reuse of organizational knowledge represented using business process models. Various studies related to managing large collections of business process models are reviewed. The core concept of business process model repository was outlined as well as the reference architecture provided in related works. This research is focused on considering the business process model repository as part of the whole architecture repository defined in the field of enterprise architecture. The knowledge-based model used to store process models, as well as the similarity measure used to identify process models in the repository that are similar to a given process model or a fragment there of are proposed. Besides that, the elaborated approach proposes the decision tree model for business process models classification according to the enterprise continuum concept of enterprise architecture, as well as the conceptual model of the business process model repository. The software prototype developed to implement the proposed approach was used to upload sample process models and estimate their similarity according to the enterprise continuum categories. The accuracy of the proposed similarity measure is analyzed for the different enterprise continuum categories of artifacts.
Keywords: business process model; similarity measure; organizational knowledge; repository; enterprise continuum